Generation of Standardized and Reproducible Forebrain-type Cerebral Organoids from Human Induced Pluripotent Stem Cells - Krefft, Olivia (J Vis Exp, 2018)
The human cortex is highly expanded and exhibits a complex structure with specific functional areas, providing higher brain function, such as cognition. Efforts to study human cerebral cortex development have been limited by the availability of model systems. Translating results from rodent studies to the human system is restricted by species differences and studies on human primary tissues are hampered by a lack of tissue availability as well as ethical concerns. Recent development in human pluripotent stem cell (PSC) technology include the generation of three-dimensional (3D) self-organizing organotypic culture systems, which mimic to a certain extent human-specific brain development in vitro. Currently, various protocols are available for the generation of either whole brain or brain-region specific organoids. The method for the generation of homogeneous and reproducible forebrain-type organoids from induced PSC (iPSC), which we previously established and describe here, combines the intrinsic ability of PSC to self-organize with guided differentiation towards the anterior neuroectodermal lineage and matrix embedding to support the formation of a continuous neuroepithelium. More specifically, this protocol involves: (1) the generation of iPSC aggregates, including the conversion of iPSC colonies to a confluent monolayer culture; (2) the induction of anterior neuroectoderm; (3) the embedding of neuroectodermal aggregates in a matrix scaffold; (4) the generation of forebrain-type organoids from neuroectodermal aggregates; and (5) the fixation and validation of forebrain-type organoids. As such, this protocol provides an easily applicable system for the generation of standardized and reproducible iPSC-derived cortical tissue structures in vitro.